Analysis of the Influence of Environmental Concern and Perceived Value on The Purchase Intention of Electric Cars with TPB Mediation Among Generation Y In Jakarta - M.Jimmy Hadi Wijaya; Didik J. Rachbini; Agus Herta Sumarto (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the influence of Environmental Concern and Perceived Value on Purchase Intention, mediated by Subjective Norm, Attitude, and Perceived Behavioral Control. The study population consists of Generation Y individuals in Jakarta, with a total sample of 385 respondents determined using Cochran's formula. The sampling technique used was purposive sampling mixed with Snowball Sampling, and data were collected through an online questionnaire distributed via Google Form. The results show that Environmental Concern has a positive and significant effect on Subjective Norm, Attitude, Perceived Behavioral Control, and Purchase Intention. All three mediating variables partially mediate the relationship between Environmental Concern and Purchase Intention. In addition, Subjective Norm, Attitude, and Perceived Behavioral Control each have a positive and significant effect on Purchase Intention. Perceived Value also positively affects Attitude and Purchase Intention, with Attitude acting as a partial mediator. All forms of mediation identified in this study are classified as partial mediation. These findings indicate that Generation Y’s intention to purchase electric vehicles in Jakarta is influenced not only by environmental concern and perceived product value, but also significantly shaped by Subjective Norm, Attitude, and Perceived Behavioral Control in the Purchase Intention to electric vehicles.